Analisis Penggunaan Pronomina dalam Tajuk Rencana Koran Harian Riau Pos - Rachman Hadi, Arief; Rahayu, Sri (UIR PRESS, 2021)
A pronoun is a pronoun that serves to replace a person, thing or something that is differentiated, pronouns are distinguished by personal pronouns. The problems in this research are (1) How to use personal pronoun pronouns in the editorial plan of the Riau Pos Daily Newspaper, (2) How to use directive pronouns in the editorial plan of the Riau Pos Daily Newspaper, (3) How to use their own pronoun pronouns in the editorial plan of the Riau Pos Daily Newspaper, (4) How do you use the pronoun pronoun in the editorial plan of the Riau Pos Daily Newspaper, (5) How is the use of conjunctive pronouns in the editorial plan of the Riau Pos Daily Newspaper and (6) How do you use indefinite pronouns in the editorial plan of the Riau Pos Daily Newspape. The purpose of this study was to collect data and information about the analysis of pronouns in the Riau Pos Daily newspaper editorial. The theory used in analyzing the problem of this research is pronouns according to H. Guntur T (2009). The method used in this research is descriptive method, this research approach uses a qualitative approach. This type of research includes literature study, as well as data collection techniques using documentation and hermeneutic techniques. The data in this study are in the form of the Riau Pos 2020 daily newspaper editorial, which consists of 26 editions. From the data analysis in this study, the authors conclude that the editorial plan of the Riau Pos daily newspaper uses the pronoun form of the self-pronoun, the directive pronoun, the owner's pronoun, the pen pronoun, the liaison and indefinite pronouns in presenting news and information to society. Keywords: pronouns and editorials